Pengaruh Indikator Relative Strength Index (RSI) dan Moving Average (MA) terhadap Keputusan Pembelian Saham di Pasar Modal Syariah Kota Bengkulu - Leonardo Duarsie Mulya Rasyid; Romi Adetio Setiawan; Miko Polindi (Universitas Muhammadiyah Surabaya, 2026)
Islamic capital markets have developed in various countries, each with unique investment characteristics. In this context, stock investment decisions in Islamic capital markets can be influenced by various factors. The purpose of this study is to determine the effect of applying technical analysis through the relative strength index (X1) and moving average (X2) indicators on stock purchase decisions (Y) in the Islamic capital market in Bengkulu City. To test this, this study used a quantitative method with primary data collection techniques in the form of questionnaires distributed to 100 respondents. The data analysis technique used was multiple linear regression using SPSS version 25.0. From the research results, the relative strength index and moving average indicators as shown by the T-test results, namely the relative strength index t-count value > t-table (5.096 > 1.660), the moving average t-count value > t-table (4.242 > 1.660), based on the research results and discussion, it is stated that the contribution of the relative strength index and moving average indicators simultaneously to stock purchase decisions is 64.3%, the remaining 35.7% is explained by other variables outside the model.